Імерсивні технології в готельному бізнесі: аналіз світового досвіду - Бондар, Наталія Петрівна; Боцян, Тетяна Вікторівна; Шаран, Лариса Олександрівна (My University, 2022)
Розкрито суть та роль імерсивних технологій в дозвіллєвій діяльності готелів, охарактеризовано основні підходи щодо їх використання. Розкрито дозвіллєвий аспект використання імерсивних технологій в готельному бізнесі. Зроблено висновок, що впровадження імерсивних технологій може розглядатись як «цифрова інновація», а впровадження цих технологій в готельному бізнесі дає змогу успішно діяти в таких сферах: маркетинг; дозвілля; навчання. Результати роботи можуть бути використані при розробці управлінських рішень щодо впровадження імерсивних технологій в діяльність готелів. Based on the analysis, the essence and role of immersive technologies in the leisure activities of hotel facilities are revealed, the main approaches to their use are described. There are three main areas of immersive technologies usage in the hotel business: marketing, leisure and education. Conclusions and discussions. The leisure aspect of immersive technologies usage in the hotel business is revealed in the article. Based on the theoretical analysis of their implementation, it is concluded that this issue is not developed in the Ukrainian scientific literature. The introduction of immersive technologies can be considered as an innovation, given that "innovation is the creation or improvement of competitive technologies (products or services), which in this period of time are implemented in the activities of enterprises." This innovation can be classified both as an innovation in the field of information technology and an innovation in the field of multimedia technology. Due to the fact, that the difference between these categories is insignificant, it is proposed in the article to combine them into one – "digital innovation". Based on the generalization, it is concluded that the introduction of virtual reality technologies in the hotel business allow hotels to operate successfully in the following areas: marketing; leisure; teaching. The results of the work can be used in the development of management decisions on the implementation of immersive technologies in hotels.
Keywords: імерсивні технології; інновації (готельно-ресторанний комплекс); віртуальна реальність; доповнена реальність; immersive technologies; дозвіллєві послуги; virtual reality; augmented reality; кафедра готельно-ресторанної справи